Health literacy and drug labeling needs identified in indigenous population of Alto Telire, Talamanca Health Area, Costa Rica - Mora Vicarioli, Rocio (2021)
Introduction: The understanding of sociodemographic characteristics, health literacy, and drug labeling needs allows to create the bases for professionals to target actions for the improvement of healthcare among vulnerable populations. Methodology: From this, a quantitative, observational research was carried out, with an exploratory scope; that addressed the indigenous population residing in the Alto Telire sector, located in the province of Limón, Costa Rica, which is characterized by its isolation and low schooling. This article presents the characterization of sociodemographic aspects, health literacy, as well as the identification of needs related to the labeling of medicines for a group of patients of the Cabécar ethnic group, attended in May 2018 by representatives of the Costa Rican Social Security Fund (CCSS). The results were obtained through direct interviews with patients. Results: The results obtained from the study highlight that 57% of the participating population is female, with ages between 18 and 45 years. Furthermore, the lack of access to education that the population had until 2009 explains why 70 42% of the participants do not have any type of education, which is related to the fact that a 100% have low health literacy level. On the other hand, participants recognize their medications principally by the name, use and physical characteristics, being the use given to the medication the main way to recognize it. Conclusions: The population included in this study has low education and an inadequate level of health literacy. Drug labeling needs are primarily related to indications and the person intended to use it. Furthermore, drug labels are the only source of information available to this population in order to rationally use their treatments.